articel Analysis Of Factors Affecting User Satisfaction Intermodal Integration Services At Cimahi City Station - Jihan Salmaa (Journal of Jabar Economic Society Networking Forum, 2025)
Cimahi City is part of the Greater Bandung metropolitan area which has a strategic role in the regional transportation system. Cimahi City has a population of 598.70 thousand people with a density of 14,110 people/km2 (BPS, 2025). The increase in population affects population mobility with an increasing demand for transportation services. Cimahi City Station is part of the transportation node which is the point of switching modes for train users and city transportation (angkot). This journal review provides results and comparisons of previous studies that discuss intermodal integration service user satisfaction, which emphasizes service quality, trust, and loyalty factors. This review also provides a study of the actual conditions in Cimahi City, such as limited bus stop facilities, uncoordinated routes, and the tendency of people to switch to online transportation due to the lack of comfort and reliability of existing services. The results of this review are expected to be the basis for designing strategies to improve integrated transportation services in Cimahi City.